Kajian Keberkesanan Penggunaan Getah dalam Pembinaan Jalan Raya - Mohd Mashuri, Muhammad Khairul Ikhwan; Shareh Musa, Sharifah Meryam; Kassim, Narimah; Zainal, Rozlin; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
In hot weather, asphalt pavement will usually harden with age and will require more frequent maintenance. Hardening of age causes the asphalt to become hard and brittle and in turn will cause the road pavement layer to become inelastic which causes it to crack and break. The problem statement for this study is the issue of damage or cracking of the road faced by the residents of the surrounding area for the use of the road for daily affairs. This problem has affected the road users where cracks, potholes, has caused uneven roads and dangerous for users who ride motorcycles so that there are accidents that occur due to road damage that occurs. There are three objectives that are focused, namely to study the potential use of rubber in road construction, to study the level of effectiveness of the use of rubber in road construction and to study measures to increase the use of rubber in road construction. The methodology of this study uses a qualitative method that is using secondary data instruments and previous studies. The scope of this study is focused on the road on Federal Road FT01 Yong Peng - Segamat from Kampung Desa Temu Jodoh to Kampung Kwong Sai, Segamat. The results of this study shown, potential use of rubber in road construction to reduce the problem of road cracks that occur after using the method of mixing natural rubber into asphalt improve the quality and quality of roads in the study area.